2020
DOI: 10.18280/isi.250405
|View full text |Cite
|
Sign up to set email alerts
|

Machine Vision Based Plant Disease Classification Through Leaf Imagining

Abstract: Plants disease identification plays a major role in agriculture yield prevention. Traditionally, manual plant surface examination is conducted which is time-consuming and relatively less efficient. Therefore, this study incorporates machine vision-based techniques, for plant disease identification (i.e. healthy leaf, Alternaria Alternate, and bacterial blight). The developed method employs a dataset comprised of more than 10,000 data points. Initially, Image processing is performed followed by image pre-proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…When Table 5 is examined, it is seen that 100% classification success is achieved for all classes and all core functions with wavelet features. It is seen that a higher success value is obtained compared to the results obtained in the previous study [30] and manual examination. Also, it seems that kernel functions do not have a direct effect on classification success.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…When Table 5 is examined, it is seen that 100% classification success is achieved for all classes and all core functions with wavelet features. It is seen that a higher success value is obtained compared to the results obtained in the previous study [30] and manual examination. Also, it seems that kernel functions do not have a direct effect on classification success.…”
Section: Resultscontrasting
confidence: 57%
“…In the studies conducted with the SVM algorithm, the effect of different kernel functions on classification success was investigated. In some studies, the RBF kernel function-based classifier was found to be more successful, and in some studies, the polynomial kernel-function classifier was more successful [25][26][27][28][29][30]. Therefore, in this study, the success of both core functions in classification was measured.…”
Section: Svm Classificationmentioning
confidence: 99%
“…With its advanced design that uses deep layers of convolutional neural networks, the DL model outperforms the SVM by a fairly large margin when it comes to how well it can classify things [70]. For linear and RBF kernels, the accuracy was 96.33% and 97%, respectively, which was even closer to that of DL.This algorithm needs data to learn from the training data, which comes from feature vectors and data outputs, which [71]. These features and labels are used to teach the SVM, which is also called the prediction model.…”
Section: Machine Learning Based Classifier Techniquesmentioning
confidence: 97%
“…Rehman et al [8] developed image processing and segmentation techniques to identify plant diseases, which is then carried out by classifying plant diseases with multi-class SVM. The results of the method developed have the ability to identify three types of diseases in plants by showing an accuracy value of 95%.…”
Section: Introductionmentioning
confidence: 99%